Case Report: ACUTE IRON TOXICITY IN SIX WEEKS OLD JUVENILE AFRICAN CATFISH (Clarias gariepinus) - Bello, Umar; Usman, Mannir Dahiru; Musa, Usman (Veterinary Biomedical and Clinical Journal, 2025)
Acute iron toxicity is an underreported cause of mortality in Aquaculture despite iron being a common groundwater contaminant in parts of sub-Saharan Africa. This case describes a sudden mortality event in six-week-old juvenile Clarias gariepinus reared in Sokoto, northwestern Nigeria. Over 50% of the 38, 000 stocked juveniles died within three days after transfer to new farm. Water analysis revealed iron concentrations from 0.57 to 0.99 mg/L, exceeding the Nigerian Industrial Standard limit of 0.3 mg/L for aquaculture water. A parallel cohort from the same batch reared elsewhere remained unaffected, ruling out infectious causes. The findings confirm acute iron toxicity as the etiology and underscore the vulnerability of early juvenile catfish to elevated iron levels. This highlights the need for routine trace metal monitoring, effective borehole water treatment, and heightened diagnostic awareness to prevent catastrophic losses in aquaculture systems.